Artificial Intelligence (AI) and Information and Communication Technology (ICT) -Based Sand Mining Supervision: A Legal Business and Maqashid Sharia Perspective - Ali, Bujang; Loin, Raymundus (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: The supervision of sand mining in Indonesia remains predominantly reliant on manual methods, which are deficient in accuracy, transparency, and effectiveness. The integration of Artificial Intelligence (AI) and Information and Communication Technology (ICT) presents an opportunity to establish a more equitable and sustainable oversight system.Purposes of the Research: This research aims to analyse the integration of AI-ICT in the supervision of sand mining in Ketapang from the perspectives of business law and maqashid syariah.Methods of the Research: This study employs a qualitative approach, utilising literature reviews, analysis of national and regional regulations, and an examination of maqashid syariah. Data are collected through legal documents, academic articles, and policy reports, and subsequently analysed using descriptive-analytical methods. Triangulation techniques are employed to ensure data validity and consistency of findings.Results Main Findings of the Research: The results of the research indicate that the integration of AI-ICT can enhance the accuracy of detecting mining activities, strengthen legal compliance, and support maqashid syariah values such as environmental protection and social justice. However, the study also identifies limitations related to digital infrastructure and the absence of specific regulations concerning the utilisation of AI-ICT within the mining sector. The integration of AI-ICT has the potential to create a more transparent, accountable sand mining supervision system that aligns with the principles of sharia justice. These findings are significant as a foundation for policy recommendations and regulatory enhancements to support the digital transformation of the mining sector.